The Effectiveness of Rewards in Shaping the Morality of Students at Elementary School Al Aulad Al Jannah: An Educational and Da'wah Approach - Najamuddin, Andi; Umrati, Umrati; Juliani, Juliani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study examines the effectiveness of rewards in shaping the morality of students at Elementary School Al Aulad Al Jannah in Wajo Regency through an educational and da’wah approach. These goals are (1) to list the learning activities that happen at the institution, (2) to look into the ways that students' morals are improved, and (3) to see how well rewards help with moral growth. This qualitative research employs educational, sociological, psychological, and da’wah perspectives. Data collection involved primary sources, including interviews with institutional leaders, teachers, parents, and students, as well as secondary data such as documentation and institutional records. Observation, interviews, and documentation were utilized as instruments, with analysis focusing on data reduction, presentation, and conclusion drawing. The findings reveal diverse learning activities, including communal prayer, Qur'anic recitation, memorization using movement and murottal techniques, congregational Asr prayers, and lessons on hadith, daily prayers, and Arabic. Lectures, demonstrations, practice, exemplary behavior, and habituation facilitate students' moral development. The implementation of rewards has proven effective, as evidenced by increased worship engagement, improved discipline in many students, and significant self-development, contributing positively to their moral character formation.